The transformation of Islamic art during the Sunni revival - Tabbaa, Yasser, 1948- (Publications on the Near East, University of Washington., 2001)
"The transformation of Islamic architecture and ornament during the eleventh and twelfth centuries signaled profound cultural changes in the Islamic world. Yasser Tabbaa explores with exemplary lucidity the geometric techniques that facilitated this transformation, and investigates the cultural processes by which meaning was produced within the new forms. Iran, Iraq, and Syria saw the development of proportional calligraphy, vegetal and geometric arabesque, muqarnas (stalactite) vaulting, and other devices that became defining features of medieval Islamic architecture.